Modelo de propagação para sistemas de telefonia móvel para guias de ondas com antenas acima do topo dos prédios - Santos, Rafael Tosta (2016)
This master thesis presents a model of deterministic propagation for waveguides with transmitting antenna above the top of the buildings and the equation for the diffraction at the top of the buildings. From the model developed by Dr. Edgar Silva Jr., adaptations are made to consider buildings of different heights along a waveguide. It is developed especially for this work calculations for diffraction at the top for a more accurate model. All the equipment and software used in the process of collection and preparation of the measured data, the sites used for model validation in the city of Feira de Santana - BA and São Paulo - SP, in Brazil, the construction of the 3D model and extraction sites database using Google Earth are described. Comparisons with measured values are show that the developed model can be a useful tool in signal envelope behavior analysis for waveguides with antennas above the top of the buildings.